2017
DOI: 10.1016/j.molp.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The DTH8-Hd1 Module Mediates Day-Length-Dependent Regulation of Rice Flowering

Abstract: Photoperiodic flowering is one of the most important pathways to govern flowering in rice (Oryza sativa), in which Heading date 1 (Hd1), an ortholog of the Arabidopsis CONSTANS gene, encodes a pivotal regulator. Hd1 promotes flowering under short-day conditions (SD) but represses flowering under long-day conditions (LD) by regulating the expression of Heading date 3a (Hd3a), the FLOWERING LOCUS T (FT) ortholog in rice. However, the molecular mechanism of how Hd1 changes its regulatory activity in response to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 59 publications
(121 reference statements)
7
110
0
1
Order By: Relevance
“…In rice under non‐inductive LD conditions, phyB has been shown to delay flowering by up‐regulating Ghd7 , thereby inhibiting expression of the flowering signal integrator Ehd1 that promotes expression of florigen genes Hd3a and RFT1 (Itoh et al, 2010; Osugi et al, 2011; Xue et al, 2008). Another major photoperiodic regulator of Hd3a expression is the rice CONSTANS orthologue Hd1, which appears to promote or repress flowering in SD or LD, respectively (Du et al, 2017; Izawa et al, 2002). We hypothesize that OsPHYB / OsYHB overexpression triggers early flowering in rice by transcriptionally/translationally regulating the Ghd7‐Ehd1‐Hd3a/RFT1 pathway and/or Hd1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In rice under non‐inductive LD conditions, phyB has been shown to delay flowering by up‐regulating Ghd7 , thereby inhibiting expression of the flowering signal integrator Ehd1 that promotes expression of florigen genes Hd3a and RFT1 (Itoh et al, 2010; Osugi et al, 2011; Xue et al, 2008). Another major photoperiodic regulator of Hd3a expression is the rice CONSTANS orthologue Hd1, which appears to promote or repress flowering in SD or LD, respectively (Du et al, 2017; Izawa et al, 2002). We hypothesize that OsPHYB / OsYHB overexpression triggers early flowering in rice by transcriptionally/translationally regulating the Ghd7‐Ehd1‐Hd3a/RFT1 pathway and/or Hd1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Hd1 is a key gene that largely determines rice photosensitivity [28]. Given that both Ghd7 and Ghd8 are involved in the Hd1-Hd3a regulatory pathway [25,29,30], we tested whether the interaction between Ghd7 and Ghd8 or Ghd7 and Ghd8 alone can affect the function of Hd1 on photosensitivity. The core collection was planted under both LD and SD conditions.…”
Section: Interaction Of Ghd8 and Ghd7 Is Pivotal For Hd1 And Hd3a To mentioning
confidence: 99%
“…Previous results have indicated that the floral transition is orchestrated by several parallel and interactive genetic pathways that are regulated by a variety of environmental and endogenous signals [1]. Many key genes and regulatory networks have been identified in herbaceous annual plants such as Arabidopsis [2,3], rice [4], gourds [5], potato [6] and sorghum [7]. However, much less 3 is known about such regulation in perennial plants.…”
Section: Introductionmentioning
confidence: 99%